2015
DOI: 10.1002/anie.201506291
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Thermally Accessible Triplet State Resulting from Rotation around a Main‐Group π Bond

Abstract: We report the first direct spectroscopic observation by electron paramagnetic resonance (EPR) spectroscopy of a triplet diradical that is formed in a thermally induced rotation around a main-group π bond, that is, the SiSi double bond of tetrakis(di-tert-butylmethylsilyl)disilene (1). The highly twisted ground-state geometry of singlet 1 allows access to the perpendicular triplet diradical 2 at moderate temperatures of 350-410 K. DFT-calculated zero-field splitting (ZFS) parameters of 2 accurately reproduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
2
26
0
2
Order By: Relevance
“…[3] Very recently,atriplet diradical arising from the twisted Si=Si bond in tetrakis(di-tertbutylmethylsilyl)disilene with as inglet-triplet splitting of 7.3 kcal mol À1 was described. [4] Dark-green, overcrowded 13,13'-bis(dibenzo-[a,i]fluorenylidene) (1), which was first described in 1925, [5] is no less fascinating (Scheme 1). Obviously,s teric strain prevents this compound from being planar.…”
mentioning
confidence: 99%
“…[3] Very recently,atriplet diradical arising from the twisted Si=Si bond in tetrakis(di-tertbutylmethylsilyl)disilene with as inglet-triplet splitting of 7.3 kcal mol À1 was described. [4] Dark-green, overcrowded 13,13'-bis(dibenzo-[a,i]fluorenylidene) (1), which was first described in 1925, [5] is no less fascinating (Scheme 1). Obviously,s teric strain prevents this compound from being planar.…”
mentioning
confidence: 99%
“…[32,33] Noteworthy in this contexti sarecent report from the groups of Sekiguchi and Apeloig, who observed that the disilene, R 2 Si = SiR 2 (R = SiMetBu 2 ), underwent thermally induced rotation to form at riplet diradical. [60] The diradical was detected by temperature-dependent EPR spectroscopy and further confirmed by quantum-mechanicalc alculations. Therefore, it can be hoped that by manipulatingt he electronic and steric properties of the substituents, as table silylene with at riplet ground state will soon be realized, which will open an ew vista in silylene reactivity.I na ddition, silylenes have also started to rival carbenes as ligandsi nt ransition-metalc hemistry,w hich is evident from the recent reports on various silylene-transitionmetal complexes that can mediate the hydrosilylation of ketones, reduction of amides, catalytic borylation of arenes, and CÀCbond formingr eactions.…”
Section: Discussionmentioning
confidence: 79%
“…Introduction of strong σ‐donor substituents (with no π‐donor property) to a Si II center has resulted in lowering the HOMO–LUMO energy gap and, thereby, enabling dihydrogen activation, a reaction that was thus‐far not known for silylene . Noteworthy in this context is a recent report from the groups of Sekiguchi and Apeloig, who observed that the disilene, R 2 Si=SiR 2 (R=SiMe t Bu 2 ), underwent thermally induced rotation to form a triplet diradical . The diradical was detected by temperature‐dependent EPR spectroscopy and further confirmed by quantum‐mechanical calculations.…”
Section: Discussionmentioning
confidence: 99%